2017
DOI: 10.1016/j.xphs.2017.04.058
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Delivery of Doxorubicin Using MITO-Porter Kills Drug-Resistant Renal Cancer Cells via Mitochondrial Toxicity

Abstract: Most anticancer drugs are intended to function in the nuclei of cancer cells. If an anticancer drug could be delivered to mitochondria, the source of cellular energy, this organelle would be destroyed, resulting in the arrest of the energy supply and the killing of the cancer cells. To achieve such an innovative strategy, a mitochondrial drug delivery system targeted to cancer cells will be required. We recently reported on the development of a MITO-Porter, a liposome for mitochondrial delivery. In this study,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 25 publications
0
19
0
Order By: Relevance
“…The combination of a highly fusogenic lipid, 1,2-dioleoyl-sn-glycero-3-phosphatidyl ethanolamine (DOPE) and a cell-penetrating peptide, octaarginine (R8) plays an essential role in the cell internalization process via macropinocytosis, endosomal escape, and mitochondrial accumulation [19]. For mitochondrial targeting cancer therapy, the MITO-Porter system has been used to significantly improve the antitumor activity of an aminoglycoside drug against HeLa cells and an anthracycline compound toward doxorubicin (DOX) -resistant renal cancer cells [47,48]. We are currently developing a novel mitochondrial targeting PDT system consisting of a newly synthesized porphyrin-type PS, namely rTPA, that will be used in combination with the MITO-Porter system.…”
Section: Validation Of Cancer Therapeutic Strategy Using Mito-porter mentioning
confidence: 99%
“…The combination of a highly fusogenic lipid, 1,2-dioleoyl-sn-glycero-3-phosphatidyl ethanolamine (DOPE) and a cell-penetrating peptide, octaarginine (R8) plays an essential role in the cell internalization process via macropinocytosis, endosomal escape, and mitochondrial accumulation [19]. For mitochondrial targeting cancer therapy, the MITO-Porter system has been used to significantly improve the antitumor activity of an aminoglycoside drug against HeLa cells and an anthracycline compound toward doxorubicin (DOX) -resistant renal cancer cells [47,48]. We are currently developing a novel mitochondrial targeting PDT system consisting of a newly synthesized porphyrin-type PS, namely rTPA, that will be used in combination with the MITO-Porter system.…”
Section: Validation Of Cancer Therapeutic Strategy Using Mito-porter mentioning
confidence: 99%
“…Biocompatible molecules can be transported in different ways, including delivery of the compound from the extracellular space to the cytosol, targeting of the mitochondria, and mitochondrial delivery by membrane fusion. Yamada et al (364) have shown the MITO-Porter system to be an excellent carrier for mitochondrial delivery of a cytotoxic agent, which represents a possible therapeutic strategy for treating drug-resistant cancers.…”
Section: Type 2 Diabetes and New Therapeutic Targetsmentioning
confidence: 99%
“…The anthracyline causes mitochondrial dysfunction, e.g., displacing α-enolase from mitochondria [30]. ATP synthesis is decreased in both the cytosol and mitochondria by DOX [90].…”
Section: Doxorubicin's Effect On Myocardial Energy Metabolismmentioning
confidence: 99%